Mapping of aetiologies of gastroenteritis: a systematic review and meta-analysis of pathogens identified using a multiplex screening array. (1st December 2020) - Meyer, Jeremy; Roos, Elin; Combescure, Christophe; Buchs, Nicolas C.; Frossard, Jean-Louis; Ris, Frédéric; Toso, Christian; Schrenzel, Jacques
Abstract: Objective: Emergence of molecular methods to screen stools could provide a more complete picture of pathogens causing gastroenteritis, allowing to adequately treat patients whenever required but, so far, no aggregate data have been released. Our objective was to report pathogens identified in patients suffering from gastroenteritis using a multiplex molecular array. Design: Medline and Embase were searched for original publications reporting pathogens identified with FilmArray GI panel in patients suffering from gastroenteritis. Proportions of pathogens were extracted and pooled using a model with random effects. Results: Fourteen studies (17, 815 patients) were included in the analysis. Among the 7, 071 patients (39.7%) with positive FilmArray, identified pathogens were EPEC (27.5%), Clostridium difficile (19.3%), Norovirus (15.1%), EAEC (15%), Campylobacter spp (11.8%), Salmonella spp (8.1%), ETEC (7.3%), Rotavirus (7.3%), Sapovirus (7.1%), STEC (5.2%), Shigella/EIEC (4.9%), Giardia lamblia (4%), Adenovirus (3.8%), Cryptosporidium spp (3.8%), Astrovirus (2.8%), Yersinia enterocolitica (1.7%), Escherichia coli O157 (1.1%), Plesiomonas shigelloides (1.1%), Cyclospora cayetanensis (0.7%), Vibrio spp (0.5%), Vibrio cholerae (0.3%) and Entamoeba histolytica (0.3%). When considering only studies with control group (microbiological examination of the stools performed by other methods), FilmArray identified at least one pathogen in 48.2% of patients versus 16.7% when using comparative diagnostic methods. Conclusions: FilmArray GI panel was positive in 39.7% of patients suffering from gastroenteritis. This proportion has to be mitigated by the carriage rates of identified organisms. Ultimately, restricted ordering of molecular panels to those patients who might benefit from specific treatment could provide medical value by swift identification of the pathogen and more targeted therapy.